Making Legs Matter: A Case for System Change and Transformation in Lower-Limb Management. (1st November 2021) - Atkin, Leanne; Bullock, Lynn; Chadwick, Paul; Elwell, Rebecca; Gardner, Sarah; Goodwin, Tracy; Hopkins, Alison; O'Connor, Christine; Sneddon, Margaret; Wiles, Kerry; Williams, Kate
Abstract : This consensus document is endorsed by The Queen's Nursing Institute (QNI) and The Queen's Nursing Institute Scotland (QNIS).